ФИЗИЧЕСКИЕ МЕХАНИЗМЫ ДЕГРАДАЦИИ И НАДЁЖНОСТЬ ПОЛУПРОВОДНИКОВЫХ ПРИБОРОВ - Жалелов, М.А.; Исмаилов, К.А.; Абдиреймова, Г.Р.; Аскаров, М. (SCIENCE and SOCIETY, 2016)
The article deals with the issues of work and reliability of semi-conductor devices. On the basis of the analysis there have been shown the degradational processes in semi-conductor
Keywords: semiconductor devices; mechanical stress; defects